Kearifan Lokal dalam Pernikahan Masyarakat Adat Untuk Pengembangan Wisata Budaya Negeri Tulehu - Safinah Yulianty Sitania; Pradina Anjarwati Sukirno; Morgan Ohiwal (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Negeri Tulehu is a village in Maluku Province, Central Maluku Regency. Negeri Tulehu is one of the customary-based villages that in daily life it is regulated in a culture that has been taught and preserved since ancient times. Marriage is one of the sacred activities in Negeri Tulehu and has been maintained to this day. The community believes that marriages carried out with a series of customs will receive blessings from the ancestors. This study aims to analyze the actual condition of local wisdom (marriage) in Negeri Tulehu, Central Maluku Regency. The research was conducted for three months from December to February 2023 covering an initial survey, collecting and processing data using the Phenomenology approach method. The result of the study showed that the marriage procedures that take place in Tulehu Country are still entrenched and are known to this day by the entire community. The 11 elements of marriage that have been preserved to date are Paharuru, Palamay, Malamait, Tauri, Hahalang, Nahusanamang, Dudu Kado, Kakopanokoi, Saudara Kawin, Pasiarere, and Pele Pintu. A series of local wisdom in marriage is a way to strengthen the ties of friendship and brotherhood of all the indigenous people of Negeri Tulehu.